2016
DOI: 10.1186/s40792-016-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of foramen of Winslow incarcerated hernia

Abstract: Foramen of Winslow hernia (FWH) is a rare and often overlooked diagnosis with a high mortality rate. Widespread availability of cross-sectional imaging allows early diagnosis and prompt management. In this setting, before ischemia occurs, explorative laparoscopy would be the most suitable approach. Experience, however, remains sparse, and technical difficulties may be encountered. This is the case of a 38-year-old Caucasian woman who presented to the emergency department for a sudden epigastric pain. Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
64
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 18 publications
1
64
0
1
Order By: Relevance
“…FOWH accounts for 0.08% of all visceral hernias and 8% of bowel obstruction secondary to internal hernias [1,2]. Historically FOWH was considered difficult to diagnose, often resulting in strangulated bowel contents at the time of presentation [3,4]. This was associated with a high mortality rate of up to 50% before the advent of more reliable imaging resources [2].…”
Section: Discussionmentioning
confidence: 99%
“…FOWH accounts for 0.08% of all visceral hernias and 8% of bowel obstruction secondary to internal hernias [1,2]. Historically FOWH was considered difficult to diagnose, often resulting in strangulated bowel contents at the time of presentation [3,4]. This was associated with a high mortality rate of up to 50% before the advent of more reliable imaging resources [2].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the key to diagnosis relies on prompt radiological findings, especially CT scans, because of characteristic findings. Classical CT scan findings are as follows: (i) mesenteric fat and vessels anterior to the inferior vena cava and posterior to the hepatoduodenal ligament; (ii) gas and/or fluid collection in the lesser sac with a “bird's beak” pointing toward the foramen of Winslow; (iii) the presence of a dilated small intestine posterior to the lesser omentum and compressing the stomach; (iv) two or more bowel loops in the subhepatic spaces; and (v) absence of the ascending colon in the right iliac fossa (if the ascending colon and cecum are involved) . So we should consider HFW in patients with internal herniation of unknown origin for precise and early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true when there is a lack of fusion between the parietal peritoneum and the cecum or ascending colon, and the ascending colon and cecum are involved. Instead of foramen closure, packing it with omentum is an option . It has been suggested that closure of the foramen may damage hepatoduodenal ligaments, leading to portal vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernia through the foramen of Winslow is an unusual condition, representing 8% of all internal hernias . A growing number of cases of herniation through de foramen of Winslow treated by a laparoscopic approach have been described in the literature, although there are no guidelines for treatment of viable herniated content or for foramen closure .…”
mentioning
confidence: 99%